Analisis Perubahan Kinerja Lalu Lintas Selama Masa New Normal Akibat Pandemi Covid-19 (Studi Kasus JL. R.A. Kartini) - Ultriyani, Resty Jenni; Sulistyorini, Rahayu; Ofrial, Siti Anugrah Mulya Putri (Universitas Lampung, 2021)
The Covid-19 virus causes a decrease in the activity of transportation movements on the R.A. Kartini. As a result of the decrease in transportation movement, it can have a positive effect, namely the reduction of traffic jams on Jalan RA Kartini. In connection with the above problems, it is necessary to study the road performance of R.A. Kartini during the new normal period which can then be compared with the road performance of R.A. Kartini during normal times, in order to find out how much changes in traffic performance on R.A. Kartini due to Covid-19. Thus, this study aims to determine the road performance of R.A. Kartini in new normal condition and normal condition. The results of this study indicate that there has been a change in the level of road services on Jalan R.A. Kartini with road service level during normal condition class D becomes class B road service level when new normal condition.Key words: Road Performance, Degree of Saturation, Traffic Volume, Capacity.